Enhancing Mathematical Problem-Solving Skills Through Flipped Classrooms and Discovery Learning: A Resilience-Based Approach for Elementary Students - Yeni Dwi Kurino; Tatang Herman; Turmudi Turmudi; Devi Afriyuni Yonanda; Yuyun Dwi Haryanti (STAI Hubbulwathan Duri, 2024)
Mathematical problem-solving skills are essential for elementary students and can be enhanced through innovative teaching approaches. This study investigates the effectiveness of Discovery Learning and Flipped Classroom models in improving problem-solving abilities among fifth-grade students. A quasi-experimental design was employed with two experimental groups: one taught using Discovery Learning and the other using the Flipped Classroom model. The study involved 60 randomly selected fifth-grade students. Data collection was conducted using pretest and posttest assessments to evaluate mathematical problem-solving skills. The results indicate that students in the Discovery Learning group demonstrated a significantly greater improvement in their problem-solving scores compared to those in the Flipped Classroom group. The findings suggest that the interactive and exploratory nature of Discovery Learning contributes more effectively to the development of critical thinking and collaborative problem-solving skills. The study highlights the potential of Discovery Learning in fostering deeper understanding and engagement in mathematical problem-solving. While the Flipped Classroom also showed positive effects, Discovery Learning proved to have a stronger impact, suggesting its suitability for enhancing problem-solving capabilities in elementary education. Discovery Learning is more effective than the Flipped Classroom in improving mathematical problem-solving skills among fifth-grade students. These findings underscore the importance of adopting active learning approaches to strengthen critical and collaborative skills in mathematics education.